Performance comparison in the Wingate test between standing and seated positions in competitive cyclists - Renato Rohsler; Fernando de Souza Campos; Pedro Rafael Varoni; Lucielle Baumann; Michelli Demarchi; Anderson Santiago Teixeira; Ricardo Dantas de Lucas; Renan Felipe Hartmann Nunes; Lucinar Jupir Forner Flores (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: The current study aimed to compare the anaerobic power output through the Wingate test in different positions, i.e., standing and seated, and identify the relationship between power-output and body mass. Methods: Eleven male competitive cyclists (age: 30.3 ± 4.7 years; body mass: 73.7 ± 7.7 kg; body fat: 11.3 ± 4.2%) were submitted to two sessions of the Wingate test (WT) in different positions, on different days. Results: The peak power (W), average power (W), relative peak power (W·kg-1), relative average power (W·kg-1), average cadence (rpm), and average velocity (km·h-1) presented significant differences in the standing position compared with the seated position (p < 0.05), 1155 ± 130 vs. 1082 ± 182 (W), 875 ± 96 vs. 818 ± 116 (W), 15.9 ± 1 vs. 15.0 ± 2 (W kg-1), 12.1 ± 1 vs. 11.3 ± 1 (W kg-1), 117.5 ± 7 vs. 109.8 ± 10 (rpm), 37.0 ± 2 vs. 34.6 ± 3 (km·h-1), respectively. However, when controlled the body mass, the differences in variables power output ceased to exist (p > 0.05). The fatigue and peak heart rate (bpm) indices did not present significant differences between the tests (p > 0.05). Conclusions: Sprint performance was improved when the WT was performed in a standing position in competitive cyclists. The study also reports the important relationship between body mass and anaerobic production capacity in the WT, emphasizing that it is desirable an increase in lean body mass and a reduction in fat mass, similar in competitions. We suggest that, for anaerobic assessment in cyclists, the standing position should be used during the WT, to determine the maximum power-output capacity.